The Association between PTPN22 SNPs and susceptibility to type 1 diabetes: An updated meta-analysis - Yu Su; Xue Li; Pei-dong Wu; Yu-Long Zhang; Peng-fei Fang; Fei-fei Wu; Xiao-feng He (PLoS ONE, 2025)
Type 1 diabetes (T1D) is a significant global health concern, characterized by the autoimmune destruction of insulin-producing pancreatic β-cells, resulting in lifelong dependence on insulin therapy. Although genetic predisposition plays a crucial role in the pathogenesis of T1D, environmental factors also contribute to its onset and progression. Recent research has identified a number of genetic polymorphisms, particularly in the protein tyrosine phosphatase non-receptor 22 gene (PTPN22), that are strongly associated with an increased risk of T1D and may serve as potential biomarkers for early diagnosis and prevention. Despite this, studies investigating the relationship between PTPN22 rs2476601 and T1D risk have consistently demonstrated an association in certain populations, whereas research on rs1310182 has yielded conflicting and less conclusive results. This study presents an updated meta-analysis of two key PTPN22 polymorphic loci — rs2476601 (C1858T) and rs1310182 (A852G) — with the aim of clarifying their associations with T1D. The analysis revealed a significant association between PTPN22 rs2476601 and an increased risk of T1D. In contrast, no significant correlation was found for rs1310182. These findings suggest that PTPN22 rs2476601 as a marker for T1D susceptibility, offering insights into the development of early intervention strategies. However, further research is required to validate these associations and deepen our understanding of the genetic factors involved in T1D pathogenesis.